Antioxidative phenolic compounds from a marine-derived fungus Aspergillus versicolor. Issue 1 (7th January 2016) - Wu, Zehong; Wang, Yongrui; Liu, Dong; Proksch, Peter; Yu, Siwang; Lin, Wenhan
Abstract: Bioassay-guided fractionation and chromatographic separation of a deep-sea fungus Aspergillus versicolor resulted in the isolation of 22 phenolic compounds, of which six were new natural products namely aspergilols A–F (1–6 ). The structures of the new compounds were determined through extensive spectroscopic analysis, including the ECD data and chemical conversion for the configurational assignment. Aspergilols A and B presented as a new scaffold with a C–C fusion of an anthraquinone and orcinol unit. The trolox equivalent antioxidant capacity (TEAC) assay indicated most of the phenolic compounds possessing antioxidant activities, while four compounds (12, 14, 21, and22 ) exerted strong free-radical scavenging effects with the TEAC values around five folds more than trolox. In addition, an Nrf2-dependent luciferase reporter gene assay revealed that compounds12–14 and17–18 potentially activated the expression of Nrf2-regulated gene. The primary structure–activity relationship was discussed. These findings provided the evidence that the deep-sea derived microorganisms are the promising and new source for the discovery of antioxidant agents. Graphical abstract: